Antioxidant and Toxic Activity of Helichrysum arenarium (L.) Moench and Helichrysum italicum (Roth) G. Don Essential Oils and Extracts - Asta Judzentiene; Jurga Budiene; Irena Nedveckyte; Rasa Garjonyte (Molecules, 2022)
Helichrysum arenarium (L.) Moench (sandy everlasting) is the only species from genus Helichrysum Mill that grows spontaneously in Lithuania. The chemical composition of the essential oils (EOs) from inflorescences and leaves of H. arenarium wild plants was analysed by GC-MS. Palmitic (≤23.8%), myristic (≤14.9%) and lauric (6.1%) acids, n-nonanal (10.4%), and trans-β-caryophyllene (≤6.5%) were the major constituents in the EOs. For comparison, the main components in EO from flowers (commercial herb material) of H.italicum were γ-curcumene (21.5%), β-selinene (13.6%), α-selinene (8.1%), β-eudesmol (8.3%), and α-pinene (6.5%). Composition of H. arenarium methanolic extracts was investigated by HPLC-DAD-TOF. The main compounds were the following: luteolin-7-O-glucoside, naringenin and its glucoside, apigenin, chlorogenic acid, arenol, and arzanol. Antioxidant activity of EOs and extracts was tested by DPPH● and ABTS●+ assays. Sandy everlasting extracts exhibited significantly higher radical scavenging activities (for leaves 11.18 to 19.13 and for inflorescences 1.96 to 6.13 mmol/L TROLOX equivalent) compared to those of all tested EOs (0.25 to 0.46 mmol/L TROLOX equivalent). Antioxidant activity, assayed electrochemically by cyclic and square wave voltammetry correlated with total polyphenolic content in extracts and radical scavenging properties of EOs and extracts. The toxic activity of EOs of both Helichrysum species was evaluated using a brine shrimp (Artemia salina) bioassay. H. italicum inflorescence EO was found to be toxic (LC50 = 15.99 µg/mL) as well as that of H. arenarium (LC50 ≤ 23.42 µg/mL) oils.